Peran Masyarakat Dalam Memantau Penggunaan Dana Desa - Boby Segah (Pencerah Publik, 2021)
This study aims to analyze the role of the community in monitoring the use of village funds. Considering that the village carries out self-government, the village administration consists of a village government which includes the village head and village officials. The phenomenon of using village funds has occurred since the distribution of funds to villages through the fantastic APBN, so there is a need for monitoring in the use of village funds. In this study, the research method used was literature study method. The literature study used is a method used to collect data or sources related to the topics raised in this paper. The literature studies obtained were sourced from various kinds such as regulations/laws, journals, books and other documentation. The results showed that the role of the community in monitoring the use of village funds was still not optimal. This is reflected in the lack of supervision from the community. This is due to the fact that public complaint channels are not well managed by all regions and the scope of evaluation and supervision by the Camat is not optimal. There is no institutional mechanism for transparency and accountability of village funds to the community.